2017
DOI: 10.1017/jfm.2017.764
|View full text |Cite
|
Sign up to set email alerts
|

Global stability of buoyant jets and plumes

Abstract: The linear global stability of laminar buoyant jets and plumes is investigated under the low-Mach-number approximation. For Richardson numbers in the range $10^{-4}\leqslant Ri\leqslant 10^{3}$ and density ratios $S=\unicode[STIX]{x1D70C}_{\infty }/\unicode[STIX]{x1D70C}_{jet}$ between 1.05 and 7, only axisymmetric perturbations are found to exhibit global instability, consistent with experimental observations in helium jets. By varying the Richardson number over seven decades, the effects of buoyancy on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…These observations were corroborated by the DNS results of Jiang & Luo (2000) and of Satti & Agrawal (2006). This is also consistent with the recent theoretical analysis of Chakravarthy et al (2018) based on global modes. However, the local stability analysis by Chakravarthy et al (2015) found that the dominant and only absolutely unstable perturbation is helical rather than axisymmetric.…”
Section: Introductionsupporting
confidence: 91%
“…These observations were corroborated by the DNS results of Jiang & Luo (2000) and of Satti & Agrawal (2006). This is also consistent with the recent theoretical analysis of Chakravarthy et al (2018) based on global modes. However, the local stability analysis by Chakravarthy et al (2015) found that the dominant and only absolutely unstable perturbation is helical rather than axisymmetric.…”
Section: Introductionsupporting
confidence: 91%
“…Such a flow configuration is typical of previous experimental studies [15,11,9,16]. Global instability has also been observed in buoyant jets [17], but is not examined in this study.…”
Section: Flow Configurationmentioning
confidence: 53%
“…1), referred to as the 'arc branch' from here on, was found to present features that suggest a resonance between the inflow and outflow boundaries. Such branches are in fact ubiquitous in many, if not all, global spectra of truncated open shear flows found in the literature: boundary layers [10,11,1], cylinder wakes [24,20], jets [22,12], plumes [4], three-dimensional boundary layers with roughness elements [19,17] -all these and many others present similar characteristic branches of eigenvalues that are often described as being highly dependent on the type or position of outflow boundary conditions. Typically, no convergence with respect to the length of the numerical box can be attained for such modes.…”
Section: Introductionmentioning
confidence: 92%